1993
DOI: 10.1007/bf00223811
|View full text |Cite
|
Sign up to set email alerts
|

RAPDs as an aid to evaluate the genetic integrity of somatic embryogenesis-derived populations of Picea mariana (Mill.) B.S.P.

Abstract: The usefulness of random amplified polymorphic DNA (RAPD) in assessing the genetic stability of somatic embryogenesis-derived populations of black spruce [Picea mariana (Mill.) B.S.P.] was evaluated. Three arbitrary 11-mer primers were successfully used to amplify DNA from both in-vivo and in-vitro material. Twenty-five embryogenic cell lines, additional zygotic embryos and megagametophytes from three controlled crosses involving four selected genotypes of black spruce were used for the segregation analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(72 citation statements)
references
References 41 publications
2
69
0
1
Order By: Relevance
“…Martins et al (2004) reported the genetic stability of micropropagated almond plants. The genetic stability of in vitro propagated Picea mariana was also reported by Isabel et al (1993) and in vitro-adventitious shoots of Pinus taeda (Tang 2001) and chestnut (Carvalho et al 2004). PCR based molecular markers including ISSR are very simple, fast, reliable, highly discriminative and inexpensive.…”
Section: Discussionmentioning
confidence: 87%
“…Martins et al (2004) reported the genetic stability of micropropagated almond plants. The genetic stability of in vitro propagated Picea mariana was also reported by Isabel et al (1993) and in vitro-adventitious shoots of Pinus taeda (Tang 2001) and chestnut (Carvalho et al 2004). PCR based molecular markers including ISSR are very simple, fast, reliable, highly discriminative and inexpensive.…”
Section: Discussionmentioning
confidence: 87%
“…Some genetic molecular markers, such as RFLP (DeVerno et al 1994), RAPD (Isabel et al 1993;Fourré et al 1997) and AFLP (Hornero et al 2001), have been used for analysis of true-to-typeness. Microsatellites can serve as highly sensitive markers for monitoring genetic variation that may signal potential deleterious mutations during in vitro culture, because they reflect a relatively high rate of mutation and corresponding degree of genetic variability (Burg et al 1999;Leroy et al 2000;Wilhelm et al 2005;Lopes et al 2006;Burg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The arm ratios and relative chromosome values did not show variation between embryogenic cultures and root tips or among the different lines studied. Recent molecular studies on genetic stability of black spruce embryogenic cultures showed no variation within the clones (Isabel et al, 1993). The basis for the apparent genetic stability of these embryogenic cultures is unknown but may be related to their embryogenic character (Eastman et a!., 1991 In herbaceous plants, however, the occurrence of…”
Section: Resultsmentioning
confidence: 99%